Nursery Rhymes - Vince, Sarah (Hertfordshire [England] : Make Believe Ideas, 2015)
Introducing a delightful collection of nursery rhymes, ideal for reading with young children. Children will adore reading the rhymes and exploring the adorable illustrations. A CD of nursery rhymes will teach children the famous melodies.
Keywords: Nursery rhymes -- Fiction; Nursery rhymes, English; Children's song